Being “geek” in digital communication: The case of Chinese online customer reviews - Chen, Long; Zhu, Hongqiang (Círculo de Lingüística Aplicada a la Comunicación, 2021)
In popular culture, the stereotypically iconized “geek” can be identified in different media narratives from mainstream television to magazines. Drawing upon insights from sociolinguistics and business communication studies, this paper attempts to identify the discursive constructs of “being geek” in Chinese digital business communication. By collecting the discourse data of online customer reviews from amazon.cn and analyzing the data based on the framework of Critical Discourse Analysis, the study investigates how linguistic mechanisms operate in the shaping of geek culture and the construction of “being geek” in the participatory communication of business. The results revealed lexical variables and generic intertextuality are prominent in the discourse construction of “being geek”, to create a stimulus for a promotional culture in business communication.